Measurement of Performance Community-Based Waste Treatment Facility (TPS 3R Saling Asih) Bandung City - Royhan, Winneyni Salsabila; Sari, Kartika Eka; Meidiana, Christia; Ismail, Hairi; Aledeh, Muhammad (Perencanaan Wilayah dan Kota FT UB, 2023)
Increasing amounts of household waste due to population growth may lead to problems if it is not accompanied by an efficient waste management system. Along with efficiency, waste management should include waste reduction which can be implemented through Reduce, Reuse, and Recycle (3R concept). 3R can be conducted in a facility called TPS3R. Bandung, one of the big cities in Indonesia has implemented 3R in TPS3R. There are a growing number of TPS3Rs being built, but most of them lack management capacity. Out of seven TPS3Rs in Bandung City, TPS3R Saling Asih has the lowest capacity to treat the waste which is only 28.89% of the total waste production in the serviced area. Therefore, this research aims to evaluate the Level of Service (LoS) TPS3R Saling Asih using indicators scored based on some criteria. The score is weighted according to the importance and the urgency. The indicators are grouped into five aspects i.e., related regulation products, technical-technological, management institutional, financial operational, and participation. The evaluation results gained a relative value of 14.25 indicating less function. The recommendations for the results were preparation for performance improvement focusing on the indicators with low values.